Cleaning up in the endoplasmic reticulum: ubiquitin in charge. - Christianson, J; Ye, Y (2014)
The eukaryotic endoplasmic reticulum (ER) maintains protein homeostasis by eliminating unwanted proteins through the evolutionarily conserved ER-associated degradation (ERAD) pathway. During ERAD, maturation-defective and surplus polypeptides are evicted from the ER lumen and/or lipid bilayer through the process of retrotranslocation and ultimately degraded by the proteasome. An integral facet of the ERAD mechanism is the ubiquitin system, composed of the ubiquitin modifier and the factors for assembling, processing and binding ubiquitin chains on conjugated substrates. Beyond simply marking polypeptides for degradation, the ubiquitin system is functionally intertwined with retrotranslocation machinery to transport polypeptides across the ER membrane.